2015
DOI: 10.3329/cmoshmcj.v14i2.25718
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome in Paraplegic Patients from Spinal Cord Injury

Abstract: Background: Patients with Spinal Cord Injuries (SCI) are confronted with motor and sensory deficits as well as bladder, bowel and sexual dysfunction, which lead to a fundamental change of life. Because of the extensive medical, emotional and social consequences of the SCI, multidisciplinary management is essential. This study focuses on the functional outcome after a spinal cord injury.Methods: This was an observational study done during a period of 6 months from July 2007 to December 2007 among paraplegic spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The Demographic variables author took into consideration were sex, age, employment status and income of the patient. Out of 201 study population 176 were male and 25 were female and this male predominance was also reported in the previous studies carried out both locally [14,[18][19][20] and globally [4][5][6][7][8][9][10][11]21] (Table 1). In this study most of the patients were in their 3 rd decade which consisted 28.6% , followed by 27.4% in between 21-30 years and 26.8% in between 41-50, which was also a common finding as reported by Hossain et al [22] where mean age was 47.44 ± 13.30 [17]; Ulrich et al found it 36.1 and according to Lali et al [21] mean age was 35.3, but in some studies the age of the study population was little bit different [4,14,16,18] (Table 1).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The Demographic variables author took into consideration were sex, age, employment status and income of the patient. Out of 201 study population 176 were male and 25 were female and this male predominance was also reported in the previous studies carried out both locally [14,[18][19][20] and globally [4][5][6][7][8][9][10][11]21] (Table 1). In this study most of the patients were in their 3 rd decade which consisted 28.6% , followed by 27.4% in between 21-30 years and 26.8% in between 41-50, which was also a common finding as reported by Hossain et al [22] where mean age was 47.44 ± 13.30 [17]; Ulrich et al found it 36.1 and according to Lali et al [21] mean age was 35.3, but in some studies the age of the study population was little bit different [4,14,16,18] (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…Out of 201 study population 176 were male and 25 were female and this male predominance was also reported in the previous studies carried out both locally [14,[18][19][20] and globally [4][5][6][7][8][9][10][11]21] (Table 1). In this study most of the patients were in their 3 rd decade which consisted 28.6% , followed by 27.4% in between 21-30 years and 26.8% in between 41-50, which was also a common finding as reported by Hossain et al [22] where mean age was 47.44 ± 13.30 [17]; Ulrich et al found it 36.1 and according to Lali et al [21] mean age was 35.3, but in some studies the age of the study population was little bit different [4,14,16,18] (Table 1). It was found that 93 of the respondent (47%) were employed and 103 were unemployed (57%) which somewhat correlate with Zahangir et al, who reported 36% of the patient to be day laborer [18] and also Ulrich et al, according to whom only 22% of the patients were full time employed but does not go in line with Lali et al and other articles [4,14,17,22] (Table 1).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…8 Following SCI, most men experience impairments in sexual function and fertility, often due to erectile dysfunction, ejaculatory dysfunction, and abnormal semen quality. 9 The level of injury in men with SCI affects erectile function, with sacral and thoracic-lumbar segments playing a modulatory role. Studies have shown that reflexogenic erections can be retained in men with complete lesions above the sacral segments, and even in those with injury to the conus medullaris and cauda equina.…”
Section: Introductionmentioning
confidence: 99%
“…Complications include diabetes, urinary tract infections (UTIs), autonomic dysreflexia, pressure ulcers, worsening spasticity, and catheter-related issues. 9 The current approach to best practices regarding sexuality and reproductive health in individuals with SCI is opinion-based and typically relies on clinical experience with small patient populations in select hospitals and rehabilitation facilities. Recognizing the importance of this topic for improving the quality of life for individuals with SCI, the consortium for spinal cord medicine has identified sexuality and reproductive health as a high priority area.…”
Section: Introductionmentioning
confidence: 99%